Metode Berpikir Deduktif dan Induktif dalam Pendidikan Agama Islam: Studi Literatur - Muhamad Rifai; Muhammad Hafiz Rivaldi; Hanifah Nurul Izzati; Azkia Aulia Rahmah; Raka Syahputra; Bina Prima Panggayuh (Advances In Education Journal, 2026)
The deductive method moves from general concepts to specific conclusions, while the inductive method builds generalizations from specific facts. Both are important for developing students’ logical and systematic thinking in Islamic Religious Education (PAI). This study aims to examine the use of deductive and inductive methods in PAI through a literature review. It uses a qualitative approach based on relevant journal sources, with descriptive-analytical techniques to evaluate their roles and effectiveness. The findings show that the deductive method is effective for teaching normative materials such as creed and sharia because it provides clear and structured understanding. In contrast, the inductive method supports the development of critical thinking and contextual understanding through real-life experiences. Therefore, combining both methods in PAI learning can create a more comprehensive, balanced, and adaptive approach that aligns with current educational needs and helps form rational and reflective religious character in students.